2020
DOI: 10.1093/cercor/bhaa272
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure of Human Corpus Callosum across the Lifespan: Regional Variations in Axon Caliber, Density, and Myelin Content

Abstract: The myeloarchitecture of the corpus callosum (CC) is characterized as a mosaic of distinct differences in fiber density of small- and large-diameter axons along the anterior–posterior axis; however, regional and age differences across the lifespan are not fully understood. Using multiecho T2 magnetic resonance imaging combined with multi-T2 fitting, the myelin water fraction (MWF) and geometric-mean of the intra-/extracellular water T2 (geomT2IEW) in 395 individuals (7–85 years; 41% males) were examined. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 87 publications
0
20
0
Order By: Relevance
“…This affects the effective transverse relaxation rate (R2*), and can be more directly measured by quantitative susceptibility mapping (QSM). In fact, most MR markers are likely sensitive to multiple biophysical mechanisms and consequently also to various microstructural features of the tissue - for example, relaxation rates may also be influenced by axon diameter and axon packing ( Lynn et al., 2020 ). The biophysical mechanisms underlying myelin-sensitive MR-modalities have been reviewed extensively elsewhere ( Does, 2018 , Edwards, Kirilina, Mohammadi, Weiskopf, 2018 , Möller, Bossoni, Connor, Crichton, Does, Ward, Zecca, Zucca, Ronen, 2019 , Novikov, Fieremans, Jespersen, Kiselev, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…This affects the effective transverse relaxation rate (R2*), and can be more directly measured by quantitative susceptibility mapping (QSM). In fact, most MR markers are likely sensitive to multiple biophysical mechanisms and consequently also to various microstructural features of the tissue - for example, relaxation rates may also be influenced by axon diameter and axon packing ( Lynn et al., 2020 ). The biophysical mechanisms underlying myelin-sensitive MR-modalities have been reviewed extensively elsewhere ( Does, 2018 , Edwards, Kirilina, Mohammadi, Weiskopf, 2018 , Möller, Bossoni, Connor, Crichton, Does, Ward, Zecca, Zucca, Ronen, 2019 , Novikov, Fieremans, Jespersen, Kiselev, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The volume of myelin in the corpus callosum increases sharply in early childhood, reaching 86% of the nal volume at the age of 5 [14,19]. We observed that the patients ≤ 5 years old had signi cantly lower MK and RK after induction, while the patients 5 years old had not undergone similarly signi cant change DKI parameters, in the genu and splenium of CC.…”
Section: Discussionmentioning
confidence: 60%
“…It has been postulated that posterior brain regions are spared from aging, compared with anterior regions, as occipital lobes showed delayed maturation compared with other lobes, supporting a ‘last-in first-out’ hypothesis of white matter maturation [21]. A study of corpus callosum regions across the lifespan also showed the inverse U-shape, with higher MWF corresponding to regions with greater axon diameter [22]. Another study employed MWI in cognitively unimpaired adults with and without the APOE4 allele.…”
Section: Agingmentioning
confidence: 98%